Effect of dietary antioxidants, training, and performance correlates on antioxidant status in competitive rowers - Braakhuis, A. J.; Hopkins, W. G.; Lowe, T. E. (International Journal of Sports Physiology and Performance, 2013)
The beneficial effects of exercise and a healthy diet are well documented in the general population but poorly understood in elite athletes. Previous research in subelite athletes suggests that regular training and an antioxidant-rich diet enhance antioxidant defenses but not performance. Purpose: To investigate whether habitual diet and/or exercise (training status or performance) affect antioxidant status in elite athletes. Methods: Antioxidant blood biomarkers were assessed before and after a 30-min ergometer time trial in 28 male and 34 female rowers. The antioxidant blood biomarkers included ascorbic acid, uric acid, total antioxidant capacity (TAC), erythrocyte- superoxide dismutase, glutathione peroxidase (GPx), and catalase. Rowers completed a 7-d food diary and an antioxidant-intake questionnaire. Effects of diet, training, and performance on resting biomarkers were assessed with Pearson correlations, and their effect on exercise-induced changes in blood biomarkers was assessed by a method of standardization. Results: With the exception of GPx, there were small to moderate increases with exercise for all markers. Blood resting TAC had a small correlation with total antioxidant intake (correlation .29; 90% confidence limits, ±.27), and the exercise-induced change in TAC had a trivial to small association with dietary antioxidant intake from vitamin C (standardized effect .19; ±.22), vegetables (.20; ±.23), and vitamin A (.25; ±.27). Most other dietary intakes had trivial associations with antioxidant biomarkers. Years of training had a small inverse correlation with TAC (-.32; ±.19) and a small association with the exercise-induced change in TAC (.27; ±.24). Conclusion: Training status correlates more strongly with antioxidant status than diet does.